Assessment of crop water requirement and irrigation scheduling for selected crops in the Kohima district, Nagaland, India - Ghanshyam T. Patle; Tome Panggeng (Water Practice and Technology, 2024)
This study was done to examine agricultural water and irrigation schedules for key crops grown in Kohima area of Nagaland, India, which has a humid subtropical climate. Climatic data over 16 years (2006–2021) were used to estimate crop water requirements using CROPWAT 8.0 model. Rice, maize, soybean, potato, cabbage, dry bean, ginger, and naga chili are the most common crops. ET0 was calculated using the FAO Penman–Monteith method and ranged from 1.41 to 3.65 mm/day. The USDA SCS approach calculated effective rainfall. The average annual ETC for rice, maize, ginger, soybean, bean (dry), potato, cabbage, and naga chili were 537.1, 305.7, 342.7, 292.2, 288.1, 364.3, 190.6, and 141 mm, respectively. Rice, maize, ginger, soybean, bean (dry), potato, cabbage, and naga chili require an average of 251.7, 54.9, 26, 73.1, 21.3, 21.9, 121.9, and 14.5 mm of irrigation each year, respectively. The crop irrigation schedules were created with 70% efficiency. The study emphasizes that irrigation must be adjusted to each crop's individual needs, whether through strategic scheduling or modifying net and gross irrigation volumes, to enhance water management and maximize crop production in the region. HIGHLIGHTS This study emphasizes water requirement and irrigation planning for the hilly district of Kohima.; This study highlights individual crop demand through strategic scheduling to maximize production.; Fulfilling Sustainable Development Goal 2 achieves food security and promotes sustainable agriculture in hilly regions of India.; Efficient irrigation management maximizes yield and minimizes water stress.; This study's findings will help in water resources planning in the Kohima region.;